2020
DOI: 10.1680/jinam.17.00033
|View full text |Cite
|
Sign up to set email alerts
|

Cost estimation of utility strikes: towards proactive management of street works

Abstract: The true (full) cost of a utility strike incident is rarely known. Generally, only the direct costs are used to measure the impact of utility strikes; the wider indirect and social costs are rarely quantified in monetary terms. Moreover, no established methodology exists to address this gap in knowledge, while access to fully documented records often presents the greatest challenge. This paper presents research that for the first time has been given access to 16 fully detailed utility strike case studies in UK… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 30 publications
0
10
0
Order By: Relevance
“…As a result, the experimental results presented in the current paper can enhance the decision making process when locating or assessing iron pipes using the GPR method by providing information on the likely electrical properties of the soil surrounding the pipe and hence the choice of GPR to be used. This information could decrease the number of hazardous and costly utility strikes as the use of unsuitable geophysical methods has been identified as one of the main causes of utility strikes (Makana et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…As a result, the experimental results presented in the current paper can enhance the decision making process when locating or assessing iron pipes using the GPR method by providing information on the likely electrical properties of the soil surrounding the pipe and hence the choice of GPR to be used. This information could decrease the number of hazardous and costly utility strikes as the use of unsuitable geophysical methods has been identified as one of the main causes of utility strikes (Makana et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…Excavation damage to underground infrastructure in particular is causing huge financial losses. Reports speak of GBP 270 million in the UK [6,22] and USD 30 billion in the US [9] annually. Of course, subsurface utility engineering (SUE) does everything to prevent damages by following established procedures.…”
Section: Introductionmentioning
confidence: 99%
“…This analysis would suggest that the true costs of the typical utility strike in the UK would be between £58,000-£217,500 [2]. In a subsequent report and based on further analysis Makana, Metje [4] re-estimated the average cost of a strike and concluded that it is~£100,000 per strike when all associated costs are included.…”
Section: Introductionmentioning
confidence: 99%